2013
DOI: 10.1111/j.1600-6143.2012.04319.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Subcutaneous Hepatitis B Immunoglobulin After Liver Transplantation: An Open Single-Arm Prospective Study

Abstract: Life-long hepatitis B immunoglobulin (HBIG) administration is a main component of prophylactic strategy to prevent hepatitis B virus (HBV) reinfection after liver transplantation (LT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 21 publications
(25 reference statements)
2
25
0
Order By: Relevance
“…The convenience of self‐administration was already demonstrated in earlier trials and confirmed in this trial .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The convenience of self‐administration was already demonstrated in earlier trials and confirmed in this trial .…”
Section: Discussionsupporting
confidence: 81%
“…As the regular intravenous (IV) administration of HBIG is inconvenient, some investigators have used intramuscular (IM) injections . Recently, subcutaneous (SC) injections were used with high success rates to increase the independency and autonomy of patients .…”
Section: Introductionmentioning
confidence: 99%
“…Different agent strengths, routes of administration, and types of AV have shown little or no effect on patient survival (25,26). The study by Angus et al (27) showed significant reduction in the rate of HBV recurrence in the first year post-LT in patients using lamivudine and HBIG.…”
Section: Discussionmentioning
confidence: 99%
“…Combination prophylaxis with low-dose IM HBIG (400-800 IU IM) decreases costs by more than 90% as compared with an IV regimen with a recurrence rate as low as 4% at 4 years [22]. More recently, subcutaneous regimens of HBIG administered 6 months after LT have proven effective as well, with some advantage in tolerability and possibility of self-administration by patients at home [23]. Degertekin et al .…”
Section: Prevention Of Hbv Recurrencementioning
confidence: 99%
“…Alternative approaches have been studied, which include the use of low-dose intramuscular (IM) HBIG [22], subcutaneous HBIG [23], withdrawal of HBIG after a finite period or prophylaxis regimens without HBIG. The ability to achieve undetectable HBV DNA before LT in the majority of patients using potent antivirals allows the use of prophylaxis regimens minimizing the dose or duration of HBIG.…”
Section: Prevention Of Hbv Recurrencementioning
confidence: 99%